The Experience of Depression during the Careers of Elite Male Athletes - Doherty, Steve; Hannigan, Barbara; Campbell, Mark J. (Frontiers in Psychology, 2016)
The topic of depression during the career of elite male athletes has been the subject of much public interest and attention in recent years. Despite numerous debates and personal disclosures within the media, there is a dearth of published research directly exploring the phenomenon. This study sought to explore how elite male athletes experience depression during their sporting careers. Eight former/current elite male athletes who had previously publically self-identified as having experienced depression while participating in sport were recruited for this study. A qualitative methodology was employed and each participant was interviewed using semi-structured interviews. Data analysis which was conducted using descriptive and interpretive thematic analysis uncovered three domains: 1) The emergence of depression 2) The manifestation of symptoms of depression and 3) Adaptive and maladaptive coping strategies in the process of recovery. Findings from the current study reveal the nature of how male athletes experience, express and respond to depression during their careers. Additionally, this is influenced by a myriad of factors embedded in the masculine elite sport environment. Implications are discussed particularly in relation to atypical expressions of depression not necessarily reflected on or in standard diagnostic criteria. Future research is encouraged to examine in depth moderating factors (e.g. athletic sense of identity and masculine elite sport environments) for the relationship between depression and participation in elite sport.